An Examination of Language Use in Online Dating Profiles - Nagarajan, Meenakshi; Hearst, Marti (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
This paper contributes to the study of self-presentation in online dating systems by performing a factor analysis on the text portions of online profiles. Findings include a similarity in the overall factor structures between male and female profiles, including use of tentative words by men. Contrasts between sexes were also found in a cluster analysis of the profiles using their factor scores. Finally, we also found similarities in frequent words used by the gender groups.